Keeping an eye on IRIS: Risk and income solidarity in OECD healthcare systems - Achim Schmid; Pascal Siemsen; Ralf Götze (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2015)
In most wealthy democracies as represented by long-term OECD-members, healthcare systems have been established which guarantee access to a broad package of health services. However, healthcare financing involves varying distributive effects and builds on different concepts of solidarity. Healthcare researchers have examined these equity issues in healthcare financing measuring the progressivity of healthcare financing using micro-level data. Most notably, the ECuity-project published progressivity indices in some European countries and the US for the late 1980s and early 1990s. Not least due to the rather complex procedure involved with the evaluation of income and expenditure surveys, such indices have been rarely calculated since. From these studies on redistributive effects, we know that the main modes of financing quite consistently correspond to different levels of progressivity. Moreover, financing modes reflect different concepts of solidarity. Therefore, we suggest an alternative indicator to explore equity issues in healthcare financing using aggregate spending and revenue data. The Index of Risk and Income Solidarity (IRIS) is based on the respective share of distinct modes of financing. We distinguish modes of financing which involve ex-ante redistribution of health risks from those which entail only ex-post redistribution or none at all. Further, we differentiate financing modes which are related to personal or household income from those which involve no income redistribution. We assume an increase of risk solidarity as well as a decline of income solidarity in the OECD-world. First of all, new and costly medical technologies drive the demand for ex-ante redistribution of health risks. At the same time, hopes to increase efficiency of healthcare provision through forms of co-payments have been disappointed. The decline of income solidarity is expected as a result of global competition. In order to reduce labour costs, OECD countries substitute social security contributions by flat-rate premiums or general taxes. In the light of global competition, governments also tend to strengthen indirect taxes since it is far more difficult to shift consumption abroad. Finally, we assume that it is easier to legitimize rising tobacco or alcohol taxes if they are ear-marked for healthcare financing. We examine these assumptions presenting time series of risk and income solidarity based on OECD health data, OECD revenue statistics and national aggregate data on healthcare financing. We cover eleven OECD countries: Australia, Belgium, Canada, Denmark, France, Germany, Japan, the Netherlands, Switzerland, the UK and the US. These countries reflect a broad spectrum of healthcare system types in the OECD-world. The observation period starts at the eve of the first oil crisis in the 1970s and ends at the onset of the Great Recession in 2009. – – In den meisten OECD-Ländern haben sich Gesundheitssysteme etabliert, die den allgemeinen Zugang zu umfassender medizinischer Versorgung sicherstellen. Die Finanzierung dieser Gesundheitssysteme hat unterschiedliche distributive Effekte zur Folge. Damit verbundene Gerechtigkeitsfragen wurden über die Messung des Progressivitätsgrades der Finanzierungs-instrumente erforscht. Insbesondere das ECuity-Project hat Progressivitätsindizes von einigen europäischen Staaten und den USA für die späten 1980er und die frühen 1990er Jahre veröffentlicht. Aufgrund der aufwändigen Berechnungsweise mit verschiedenen Individualdatensätzen wurden solche Indizes seither selten veröffentlicht. Auf Grundlage dieser Studien ist dokumentiert, dass die Finanzierungsquellen der Gesundheitssysteme mit unterschiedlichen redistributiven Effekten verbunden sind. Wir nutzen diese Informationen, um aus Aggregatdaten einen Indikator zu bilden, der Umverteilungswirkungen in der Finanzierungsdimension des Gesundheitssystems abbildet. Dabei unterscheiden wir auf der einen Seite Finanzierungsformen, die eine Umverteilung des Krankheitsrisikos bedeuten und auf der anderen Seite Finanzierungsformen, die eine Einkommensumverteilung einschließen, indem sie höhere Einkommen zumindest proportional stärker belasten. Aus dem Anteil der so charakterisierten Finanzierungsformen entwickeln wir einen Index der Risiko- und Einkommenssolidarität (IRIS). Ausgehend von einer starken Nachfrage nach Risikoumverteilung, um den Zugang zum Gesundheitssystem bei steigenden Kosten und Bedarfen zu gewährleisten, vermuten wir einen langfristigen Anstieg der Risikosolidarität. Dahingegen könnte die Einkommenssolidarität aufgrund von internationalem Wettbewerb um Investitionskapital schwächer werden. Diese Annahmen werden für 11 OECD-Länder (Australien, Belgien, Dänemark, Deutschland, Frankreich, Japan, die Niederlande, Kanada, die Schweiz, das UK und die USA) und einen Beobachtungszeitraum von 1970 bis 2009 untersucht.
Keywords: 300